Diastolic cardiac function in connective tissue dysplasia - Yu. V. Tereschenko; G. I. Nechaeva; V. V. Potapov; M. I. Shupina; E. N. Loginova; E. V. Nadey; T. P. Kabanenko (Лечащий Врач)
The article analyzes literature data on the diagnostics of diastolic function condition in young patients with signs of connective tissue dysplasia. The problem of diagnostics of pre-clinical left-ventricular diastolic dysfunction was discussed, as well as possible influence of peculiarities of connective-tissue cardiac frame in patients with connective tissue dysplasia on functional condition of auricles and left-ventricular diastolic function.